Students’ Mathematics Reasoning Ability Reviewing from Learning Interest of Students at SMPN 16 Pekanbaru - Dewi Yuliani (Journal of Research on Mathematics Instruction (JRMI), 2021)
This research .is.motivated. by the. existence of. facts. in the.field.which. show.the.low.mathematical.reasoning.skills found in students at SMP Negeri 16 Pekanbaru. One thing that students must master to achieve learning goals is mathematical reasoning abilities. In other words, students can use mathematics as a reasoning tool both in learning mathematics in class and everyday life. This research aims to determine the difference between students' mathematical reasoning abilities and low learning interest. Good student learning interest will make students happy to learn mathematics without coercion, with good learning interest will affect students' mathematical reasoning abilities. Mathematical reasoning abilities can be improved through increasing student interest in learning. This research is a qualitative descriptive study, the population in this study were all eighth-grade students of the 2020/2021 academic year. The sample taken was class VIII.2 using a random cluster. Data collection techniques and research instruments are tests of mathematical reasoning abilities on quadrilateral material, questionnaires in questionnaire sheets for learning interests, and interviews. Based on the results of data analysis, it can be concluded that: 1) There are differences in mathematical reasoning abilities between students who have high learning interests. 2) There are differences in mathematical reasoning abilities between students with low interest in learning.